2019
DOI: 10.1021/acsbiomaterials.8b01254
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biomedical Applications of an Alkylated Quercetin–Gadolinium Complex

Abstract: Flavonoids and their derivatives have been extensively studied for their pharmaceutical applications due to their antioxidant and anti-inflammatory properties. The coordination complexes of several flavonoids have demonstrated DNA binding ability that can confer anticancer properties. The structure of the flavonoid has a pronounced influence on its pharmacological properties. Herein we report the synthesis and characterization of alkylated quercetin and its complex with gadolinium. The structure of the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Herein, a red shift (∼12 cm −1 ) of the characteristic peak of GPB 0.5 and improved intensity of the peak at 1612 cm −1 due to overlap of δ (N–H) and ν (CO) confirms the successful loading of Qu onto the surface of GPB 0.50 @PDA@PEG@HA. 57 Besides this, the optical absorption spectra of bare Qu exhibits an absorption band, centered at 382 nm (Fig. 5(d)), while the peak gets shifted to 338 nm for GPB 0.50 @PDA@PEG@HA@Qu, corroborating successful loading.…”
Section: Resultsmentioning
confidence: 61%
“…Herein, a red shift (∼12 cm −1 ) of the characteristic peak of GPB 0.5 and improved intensity of the peak at 1612 cm −1 due to overlap of δ (N–H) and ν (CO) confirms the successful loading of Qu onto the surface of GPB 0.50 @PDA@PEG@HA. 57 Besides this, the optical absorption spectra of bare Qu exhibits an absorption band, centered at 382 nm (Fig. 5(d)), while the peak gets shifted to 338 nm for GPB 0.50 @PDA@PEG@HA@Qu, corroborating successful loading.…”
Section: Resultsmentioning
confidence: 61%
“…It was reported that the chemical reaction of iron (III) at the catechol site of gallic acid, gallic acid methyl ester, and catechin resulted in characteristic absorption peaks of 415 nm and 690–695 nm [ 57 ], while the chemical reaction of iron (III) at the hydroxychromone site of quercetin revealed an absorption peak of 420 nm [ 22 ]. On the other hand, the complex of Gd (III)-quercetin, whose complex site is located at C 4 on ring C and C 5 on ring A of quercetin, did not reveal an absorption peak at a wavelength higher than 450 nm [ 46 ]. The complex between iron (III) and 3, 5, 7-tri-O-methyl-quercetin (free -OH at the catechol site) revealed a characteristic absorption peak of 600 nm [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 H-NMR spectra for pristine TPU filament were recorded using the JEOL NMR 600 MHz instrument with tetramethyl silane (TMS) as the reference (δ = 0 ppm). Approximately 50 mg of TPU filament was dissolved in 1 ml of deuterated DMSO (DMSOd 6 ) solvent, and the spectra were analyzed by Delta 5.3.1 software to predict the chemical structure of the TPU filament [17].…”
Section: Tpu Filament Characterization 221 Proton-nuclear Magnetic Re...mentioning
confidence: 99%